Intra-molecular properties of DMeOPPV studied by quantum molecular dynamics - Correia, Helena M. G. (2005)
Introducing methoxy electron donor groups into a poly(para-phenylene vinylene) (PPV) chain will lead to the appearance of unique electronic properties at the molecular scale which should affect the overall properties of light-emitting diodes based on these polymers. Self-consistent quantum molecular dynamics calculations have been used to provide information on intra-molecular properties of poly(2,5-dimethoxy-para-phenylene vinylene) (DMeOPPV), which are relevant for the modelling and characterization of polymer light-emitting diodes at nanometric length scale. We focus our attention on those properties that have been somewhat neglected in previous literature: the charge distribution associated with positive and negative charge carriers and their intra-molecular mobility when an electric field is applied.